Differences in body composition measured using the bioelectrical impedance analysis with steel and gel electrodes – on an example of professional fencers - Mizera, Olga; Mróz, Anna; Kozlowska, Lucyna (Journal of Education, Health and Sport, 2018)
Introduction: Regular assessment of body composition in athletes is a key element of their nutritional status and general condition monitoring. Purpose: Analysis of differences in the impedance (I) and body composition measurements performed by the use of analyzers with a constant current frequency of 50 kHz with steel and gel electrodes. Material and methods: Analysis were performed in experienced fencers by the use of analyzers: Tanita BC418MA (aT) with steel electrodes (eT) and Akern BIA101ASE (aA) with gel electrodes (eA, eL, eT). During the first stage of the study in 48 athletes I, fat mass (FM) and fat free mass (FFM) were measured using aA with eB in a supine position and after 3 min using aT with eT in a standing position. Then 10 fencers were randomly selected. For them measurements were performed after 10, 13 and 16 min in a supine position using eA, eL, eB and then after 3 min in a standing one using eT. Intrinsic impedance of the 3 types of gel electrodes (eA, eL, eB) were measured using aA. Results: The first stage. Differences in I, FM and FFM between eT and aA were observed (women: 101.4±52.2Ω, 1.2±2.1kg, -1.2±2.1kg, men: 98.8±27.5Ω, 1.1±1.5kg, -1.1±1.5kg, respectively). The second stage. In the subsequent measurements, differences in I were observed (women: eL-eA 3.8±1.8Ω, eB-eA 26.1±8.0Ω, eT-eA 154.4±40.6Ω;, men: of -0.7±9.4Ω, 11.1±9.2Ω, 107±36.3Ω, respectively). In both subgroups along with the increase in I, FM also increased, while FFM decreased. Intrinsic impedance of the applied gel electrodes was measured and the differences between the results were reported (eL-eA 41.1±22.0Ω, eB-eL 138.4±20.7Ω, eB-eA 179.5Ω). As the intrinsic impedance of gel electrodes increased, an increase in the whole body I was observed. Conclusion: It seems that the observed differences in the whole body impedance were not only a simple effect of changes in a body position but they might have also been related to the intrinsic impedance of electrodes.